Microclima e oleosidade da pele em calcâneos de indivíduos hospitalizados em unidade de terapia intensiva - Silveira, Lidiana Batista Teixeira Dutra (2018)
The skin microclimate (temperature and moisture) is one of the factors that predispose the development of pressure injuries (PI). The microclimate is considered the relationship between moisture/moisture or temperature/moisture of the skin surface with some factors, such as the support surfaces or the room, the use of bed and sheets, some medical devices, and the temperature of hospital rooms. The theme of this research is the skin microclimate, and its study object is the heels skin microclimate of individuals hospitalized in intensive care unit (ICU) with high or very high risk of developing PI, upon the Braden scale. The dissertation is linked to the Research Group Trabalho, Saúde, Educação e Enfermagem – Line of Research Gestão e Atenção em Saúde e Enfermagem of the Postgraduate Program in of the Federal University of Santa Maria. There is as research question: what is the heels skin microclimate (temperature and moisture) of individuals hospitalized in the ICU, and what are the factors associated with the microclimate? There is the hypothesis that the heels skin temperature of individuals hospitalized in the ICU is around 30ºC and the skin moisture around 17%. As factors associated, medical diagnosis, associated diseases, room temperature and humidity, drugs, and the use of medical devices. The general objective is to evaluate the heels skin microclimate (temperature and moisture) of individuals hospitalized in the ICU with high or very high risk of developing PI, upon the Braden scale. The specific objectives are these: to describe the heels skin temperature of individuals hospitalized in ICU; to describe the heels skin moisture of individuals hospitalized ICU; and to analyze the factors associated with the heels skin microclimate of individuals hospitalized in the ICU. This is a secondary study, which consists of extracting data collected in another original research with different investigative question. Data collection was performed from July 2017 to May 2018 and reached the sample size previewed. The results were presented in two articles format. One hundred eighty and six individuals were evaluated for eligibility, and after the application of the selection criteria, 98 patients were included, but three were excluded from the analysis due to missing data in data collection. The sample was composed of 95 patients (190 heels). It was verified that the majority were male (n=54;56.8%), Caucasian (n=82;86.3%), with mean age of 55.2±19.0 years. There is correlation between temperature, moisture and oiliness from heel and instep. There is positive correlation between heel and instep temperature (r=0.870; p<0.001); heel moisture and oiliness (r=0.916; p<0.001); heel moisture and instep oiliness (r=0,259; p<0.001); heel oiliness and instep moisture (r=0.239; p=0.001); instep moisture and oiliness (r=0.799; p<0.001). It was concluded that there is no statistically significant difference between heel skin temperature, moisture and oiliness and the body sides (right and left).